Effect of Curcuma longa L. extract on noninvasive cardiovascular biomarkers in hypertension animal models - Patonah Hasimun, Agus Sulaeman, Arif Hidayatullah, Yani Mulyani (Journal of Applied Pharmaceutical Science, 2021)
Arterial stiffness and QRS-T angle (the spatial angle between the vectors of the T-wave and QRS loops on typical electrocardiogram) are essential biomarkers for estimating the risk of cardiovascular events in hypertensive patients. Turmeric or Curcuma longa L., which belongs to the Zingiberaceae family, is reported to have antihypertensive activity. However, its effect on these biomarkers is unknown. This research investigates the antihypertensive effect of turmeric extract on arterial stiffness and frontal plane QRS-T angle in hypertensive animal models. High blood pressure was induced by a high-fat and high-fructose (HFHF) diet for 28 days in male Wistar rats. A daily dose of turmeric extract (50, 100, and 200 mg/kg) or captopril was administered to hypertensive animals for 14 days. Blood pressure, arterial stiffness, heart rate (HR), QRS-T angle, and nitric oxide (NO) levels were evaluated. An HFHF diet triggers a decrease in NO serum levels resulting in significantly increased arterial stiffness, which correlates with increased systolic blood pressure and diastolic blood pressure due to ventricular dysfunction supported by the wide QRS-T angle, and also increased HR. Turmeric extract significantly enhances the bioavailability of NO vasodilators, effectively reversing all the hypertensive-induced changes studied. This extract is helpful as a vasodilator that lowers blood pressure by repairing arterial stiffness and preventing ventricular dysfunction of the heart.
Keywords: Curcuma longa L. (Zingiberaceae), hypertension, arterial stiffness, QRS-T angle, nitric oxide.